2000
DOI: 10.1097/00063198-200009000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease in systemic lupus erythematosus

Abstract: Systemic lupus erythematosis (SLE) is a heterogenous disease of unknown etiology. It is not uncommon to see pleuropulmonary involvement in isolation or along with the involvement of other organ systems in SLE. Pulmonary manifestations of SLE can involve the pleura, lung parenchyma, airways, pulmonary vasculature, and the respiratory muscles. In this review we discuss two important pulmonary manifestations of SLE: acute lupus pneumonitis and diffuse interstitial lung disease. These two conditions have a major i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 29 publications
1
70
0
6
Order By: Relevance
“…(Boulware & Hedgpeth, 1989) A more recent review confirmed this association (Mochizuki et al, 1999) The high frequency of anti-Ro/SSa antibodies raises the possibility of their role in the pathogenesis of ALP. (Cheema & Quismorio, 2000) Prognosis is poor, with mortality reaching up to 50% as reported in an old study. (Matthay et al, 1975) The outcome is worse if ALP occurs postpartum.…”
Section: Pleural Diseasesmentioning
confidence: 96%
See 1 more Smart Citation
“…(Boulware & Hedgpeth, 1989) A more recent review confirmed this association (Mochizuki et al, 1999) The high frequency of anti-Ro/SSa antibodies raises the possibility of their role in the pathogenesis of ALP. (Cheema & Quismorio, 2000) Prognosis is poor, with mortality reaching up to 50% as reported in an old study. (Matthay et al, 1975) The outcome is worse if ALP occurs postpartum.…”
Section: Pleural Diseasesmentioning
confidence: 96%
“…Pulmonary fibrosis affects 18% of patients above 50 years compared to 2% of patients under 18 years. (Cheema & Quismorio, 2000) Clinically, patients usually present with gradually progressive shortness of breath. Chronic dry cough can be the initial presentation in some patients.…”
Section: Diffuse Alveolar Hemorrhagementioning
confidence: 99%
“…Kezelésében a nagy dózisú kortikoszteroid adását javasolják, amelynek dózisa 1-2 mg/kg/nap. Súlyos és szteroidrezisztens esetekben javasolható azathioprin-, cyclophosphamid-, IVIG-kezelés és plazmaferézis monoterápiában, illetve sikertelenség esetén kombinálva [33][34][35].…”
Section: Akut Lupus Pneumonitisunclassified
“…Az SLE-asszociált ILD megjelenése általában az idősebb, férfi betegekben gyakoribb [35]. Diffúz ILD vagy krónikus pneumonitis a betegek 3-8%-ánál fordul elő [36].…”
Section: Sle-asszociált Interstitialis Tüdőbetegségunclassified
“…Given the patient's multiorgan inflammation attributable to SLE, acute lupus pneumonitis was considered; however, acute lupus pneumonitis is an uncommon manifestation of SLE (6). It is typically a diagnosis of exclusion that is considered as the cause of hypoxia in SLE only after infectious and other etiologies have been excluded.…”
Section: Acute Lupus Pneumonitismentioning
confidence: 99%